A Systematic Review Analysis For Quran Verses Retrieval - Muhammad Afifi Mohamad Safee; Madihah Mohd Saudi; Sakinah Ali Pitchay; Farida Hazwani Mohd Ridzuan (Medwell Journals, 2024)
Volume: 11 Issue: 3